(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Acute necrotizing ulcerative gingivitis or Vincent’s stomatitis is a painful infectious condition of gingiva due to endogenous bacteria. It is an uncommon disease of gingiva, usually seen in patients with impaired immunity, whichmay be due to some underlyingsystemic diseases such as HIV infection, malignancy, or diabetes mellitus. Rarely, it is also seen in immunocompetent patients living a stressful life. Here, we report a case of Vincent’s stomatitis with the acute ulcerative involvement of gingiva in a general medical practitioner living a busy life.